2007
DOI: 10.1080/02705060.2007.9664181
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Epipelic Diatom Taxa (Bacillariophyceae) and Nutrients in Two Karstic Lakes in Central Anatolia, Turkey

Abstract: The relationship between epipelic diatom communities and 16 environmental variables from two gypsum karstic lakes in central Anatolia was explored using canonical comes ondence analysis. Temperature, ammonium (NH~+), sulphate (SO:) R and calcium (Ca ) concentrations were the most important variables related to species distribution. The genera Mastogloia, Gomphonema, Navicula, Cyrnbella, and Nitzschia were the richest in taxa. Diatom species associated with temperature, NH4+, SO^^., and ca2+ gradients were Mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The Refs. [37,38] reported that the collected seasonal epipelic diatom samples were correlated with a combination of environmental variables such as temperature, the concentrations of nitrite, and percentage of total organic carbon in the sediment.…”
Section: Phytoplankton/algal Ecology In Lake and Reservoir Managementmentioning
confidence: 99%
“…The Refs. [37,38] reported that the collected seasonal epipelic diatom samples were correlated with a combination of environmental variables such as temperature, the concentrations of nitrite, and percentage of total organic carbon in the sediment.…”
Section: Phytoplankton/algal Ecology In Lake and Reservoir Managementmentioning
confidence: 99%
“…The relationship between epipelic diatom communities and 16 environmental variables from two gypsum karstic lakes in the Sivas basin was explored by Sivaci et al (2007). The authors indicate that temperature, ammonium (NH 4 ?…”
Section: Scientific Significancementioning
confidence: 99%
“…The authors indicate that temperature, ammonium (NH 4 ? gradients are Mastogloia braunii, Mastogloia smithii var, lacustris, Campylodiscus clypeus, Navicula salinarum and Amphora coffeaeformis (Sivaci et al 2007). Sivaci et al (2008) reported that seasonal variation in the composition and concentration of epiphytic diatoms from a Great Lota lake in the Sivas basin that has a distinctive ionic character was investigated during October 2000 and October 2001, and 66 diatom taxa belonging to 24 genera were identified in the lake.…”
Section: Scientific Significancementioning
confidence: 99%